ORBITAL DEBRIS MITIGATION: PERSPECTIVE FROM ENVIRONMENTAL LAW - Parveen, Huma; Verma, Rajesh Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Orbital debris from spacecraft, has been circling Earth for over 50 years. Humans have launched objects into space, and most of them fall back to Earth daily. These debris either land or burn up in the atmosphere. Most return to Earth end up in water, which makes up 70 percent of Earth's surface. However, many of these objects remain in orbit around Earth. Space debris poses a significant threat to outer space activities, ranging from tiny paint flakes to intact, nonfunctional spacecraft and rocket bodies. The increasing amount of debris increases the risk of collision with operational satellites, highlighting the need for sustainable solutions. The evolution of the space object environment is causing an uncontrolled population growth due to increasing collisions, primarily among debris. To preserve the space environment for future generations, it is crucial to address the debris problem. International space law, including Article IX of the Outer Space Treaty, obligates states to avoid harmful contamination of outer space. These norms are more effective when considering sustainable development principles and intra- and inter-generational justice. As debris pollution increases, questions of liability and responsibility become more relevant. The Liability Convention provides a remedy for victims of damage caused by space debris, with absolute liability for damage on Earth's surface. International responsibility law also allows states to be held accountable for environmental pollution events, including a duty to active debris removal. While international law is effective in addressing the debris problem, growing use and dangers necessitate the status quo of a complete site visitors control regime for outer space.. This would strengthen the rule of law in outer space and ensure the sustainability of space utilization.